Breaking the Silence, Healing the Mind: A School Safety Socialization on Bullying, Intolerance, and Violence for Mental Health Resilience at SMP Negeri 1 Mori Atas - Yulian Heiwer Matongka; Suwarty Nursahara; Andika P. Kongah; Avvareld G. Mareoli; Baiq Emy Nurmalisa (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2026)
Bullying, intolerance, and violence in schools threaten adolescent mental health, academic performance, and social development. This community service program aimed to enhance students' understanding of these issues and foster mental health resilience through targeted socialization at SMP Negeri 1 Mori Atas. The program employed a structured three-phase methodology: planning, implementation, and evaluation. The implementation was conducted on December 9, 2025, involving 55 seventh-grade students, utilizing interactive PowerPoint presentations, educational videos, and participatory discussions. Evaluation was conducted through direct observation of students' cognitive, affective, and behavioral outcomes. Results demonstrated that 85% of students accurately identified behavioral typologies and impacts of bullying, sexual violence, and intolerance; 76% expressed empathy and rejection of discriminatory behaviors; and 82% verbally committed to reporting incidents and promoting tolerance. Students actively participated in discussions, posed critical questions, and shared personal experiences, indicating the program successfully created a safe environment for disclosure and learning. These findings confirm that participatory, multi-method socialization effectively improves cognitive awareness and fosters positive attitudinal shifts among early adolescents. The program underscores the critical importance of proactive educational interventions in protecting adolescent mental health and transforming schools into safe, inclusive, and character-driven learning environments. To sustain these outcomes, it is recommended that the school institutionalize periodic reinforcement sessions and establish student-led peer support mechanisms for long-term prevention of the three major sins of education